Pengurangan Yellow Reject pada Proses Hexavalent Chrome Plating on Plastic dengan Menggunakan Pendekatan DMAIC - M. Yani Syafei; Sophia Louren (President University, 2020)
Product quality is one of the important aspects for the company because it involves the existence, performance, productivity and profit of the company. Quality is obtained by having quality control to minimize products and produce products according to specifications. PT. Mitra Part Perkasa as a company that provides a service of chrome plating on plastics. The company is having a new quality issue of new reject that happened on hexavalent chrome process, namely yellow reject during September and October 2019 which had never happened before. The percentage of yellow rejects that happened was more than company tolerant limits of 1.5%. To overcome this problem, using DMAIC is applied to reduce the number of rejects. The first step of DMAIC is the goal of the problem and agreed upon research objectives. The second step is to measure current quality with a control chart and decide yellow rejects as the main focus of research using pareto diagram. The third step is to analyze the yellow root causes using why why analysis and fishbone diagram. The fourth step is improvement based on each factor, man, material, method, and machine. The last step is control, this step will show the results of the improvements indicated by before the repairs were made. Based on the results, the percentage of yellow reject decreased from 2.77% to 0.55% and it can be concluded that DMAIC has succeeded in reducing yellow rejects.